PRIVATE INTERNATIONAL LAW AND THE JUDICIARY - Peruana de Derecho Internacional, Sociedad (2020)
How a Court of Law and a State entity by prejudices rushed into ignoring peruvianrules of Private International Law and committed the crime of prevarication.